The Northcote History Group - Northcote History Group (Northcote, Vic. : Northcote History Group, 1999)
Arising from the demise of the Northcote Historical & Conservation Society, the aim of the Northcote History Group is to document and preserve the history relating to the former City of Northcote. History can be in a wide variety of forms including photographs, letters, articles, oral records, etc. The group fosters an understanding of the history of the people, places and things pertaining to Northcote, Fairfield, Alphington, Westgarth & Thornbury.
Title from home page (viewed on 5 Dec., 2006).
Text and graphics.
Mode of access: World Wide Web
Selected for archiving
Keywords: Northcote History Group; Northcote (Vic.) -- History